2000
DOI: 10.1053/jlts.2000.9743
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Cognitive Function of Liver Transplant Patients: A Prospective Study

Abstract: The presence of cognitive impairment in end-stage liver disease is well recognized, as are patient reports of an impoverished quality of life. The aim of this study is to systematically evaluate the effect of orthotopic liver transplantation (OLT) on these factors. Thirty-two adult patients activated for OLT participated in the study. Assessments were made on activation and at 1, 3, and 9 months post-OLT, with 24 transplant recipients available for reassessment at 9 months. Two control groups (10 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 36 publications
2
45
1
4
Order By: Relevance
“…Kober et al 20 found that the QOL reported by men was less than the one reported by women, whereas in a later study Moore et al did not find any difference. 21 Results of QOL studies that used different tools should be compared with caution, however. 22 As in most of the studies published, we found that overall, LT improves the QOL of patients considerably as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Kober et al 20 found that the QOL reported by men was less than the one reported by women, whereas in a later study Moore et al did not find any difference. 21 Results of QOL studies that used different tools should be compared with caution, however. 22 As in most of the studies published, we found that overall, LT improves the QOL of patients considerably as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cognitive deficits detectable in patients with end-stage liver failure improve after transplantation, [5][6][7][8] but whether this improvement is maintained in the long term is unknown.…”
mentioning
confidence: 99%
“…In another composite analysis published in 1999, Bravata et al concluded that there were no differences between the sexes in post-LTx QOL, although the authors commented on the scarcity of studies dealing with this topic (Bravata et al, 1999). Moore came to the same conclusion in a single-center prospective study of 10 LTx recipients compared to normal controls (Moore et al, 2000).…”
Section: Gender Differencesmentioning
confidence: 95%